1675 ABCDE vasodilator stress echocardiography in non-ischemic heart failure. (17th January 2020) - Kuznetsova, N; Borguezan Daros, C; Zanella, H; Ciampi, Q; Cortigiani, L; Gaibazzi, N; Zagatina, A; De Castro E Silva Pretto, J L; Djordjevic-Dikic, A; Simova, I; Amor, M; Merlo, P M; et al.
Abstract: OnBehalf: Stress Echo 2020 study group of the Italian Society of Cardiovascular Imaging Background: ABCDE-stress echocardiography (SE) may explore different aspects in the heterogeneous entity of known or suspected heart failure (HF). Aim: To assess ABCDE-vasodilator SE in non-ischemic HF Methods: In a prospective, observational, multicenter study, we recruited 428 patients with angiographically normal coronary arteries: 148 patients with HF and preserved (>50%) ejection fraction (HFpEF, Group 1); 100 with HF and mid-range (40-50%) ejection fraction (HFmrEF, Group 2); 180 with HF and reduced (<40%) ejection fraction (HFrEF, Group 3). A group of 75 healthy asymptomatic patients (30 male, 40%, age 57 ± 14 years) referred to testing for screening was also selected (Controls). All patients underwent vasodilator SE with dipyridamole (0.84 mg/kg) in 14 accredited laboratories of 5 countries (Argentina, Brasil, Russian Federation, Serbia and Italy). The ABCDE-SE protocol was adopted: A for regional wall motion abnormalities; B for B-lines (positivity criterion: stress ≥ rest for ≥ 2 points in a 4-site simplified scan available in 181 pts and 10 controls); C for left ventricular contractile reserve (LVCR) based on force (systolic blood pressure/end-systolic volume, positivity criterion: peak/ rest ≤1.1); D for pulsed wave Doppler-based assessment of coronary flow velocity reserve (CFVR) in left anterior descending coronary artery (positivity criterion: peak/rest ≤2.0); E for EKG-based assessment of heart rate reserve (positivity criterion: peak/rest ≤1.22). Results: All positivity criteria, except A, were more prevalent (p<.01) in Group 3 compared to Group 2, in Group 2 compared to Group 1, and Group 1 compared to controls: see figure. In particular, a blunted heart rate reserve was found in 4/75 controls (5%), 27/148 pts of Group 1 (18%), 28/100 of Group 2 (28%) and 98/180 of Group 3 (54%). Conclusions: ABCDE-vasodilator SE can help to identify the profound pathophysiological heterogeneity underlying a similar clinical presentation in patients with known or suspected HF with angiographically normal coronary arteries. These patients rarely show stress-induced regional wall motion abnormalities (A), but may exhibit pulmonary congestion (B), reduced myocardial functional reserve (C), altered coronary microcirculation (D) and cardiac autonomic dysfunction (E).